Influence of Leadership Style: A Review - et al., Divya Jyoti Thakur (International Journal of Advanced Science and Technology, 2020)
The motive of this study is to survey how an individual's style of leadership straight influence their capacity to successfully oversee their employees. It also helps to explore different views as to whether or not leaders are born to lead, or whether it is an ability that can be built and improved over time by individuals who have the desire to be successful in leadership roles.